Sociology of deviant behavior - Clinard, Marshall B.; Meier, Robert F. (Cengage Learning, 2016)
SOCIOLOGY OF DEVIANT BEHAVIOR hits the hot topics from terrorism to white-collar crime and shows you how sociological theory explains them. You'll read about justified deviance (e.g., terrorism); corporate crime and mistakes, such as the General Motors ignition problem; the changing moral landscape regarding gay marriage and marijuana use; the importance of social media in facilitating deviant acts; political crime, and more. Now in its fifteenth edition, this book continues to be the leader in its market. When you read it, you'll see why.